POLITICAL COERCION IN THE REFORMATION ERA IN BULELENG REGENCY IN THE PERSPECTIVE OF CULTURAL STUDIES - Made Suputra, Pande; Bawa Atmadja, I Nengah; Parimartha, I Gede; Ardika, I Wayan (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2011)
During the reformation era much political coercion took place in Buleleng Regency, Bali.Such political coercion occured repeatedly in the general election referred to as Pemiluconducted in 1999 and 2004, and in the election conducted to directly vote for district headsreferred to as Pilkada in 2007. It is interesting to investigate this phenomenon. The problems inthis study are formulated as follows: (1) what factors causing political coercion to take place inthe general election and in the election conducted to directly vote for district heads; (2) how ittook place; and 3) what ideology leading to it and what implications it had on the socio-cultureof the people living in Buleleng Regency?The practical theory, the theory of coercion and the theory of ideology were eclecticallyadopted to establish and analyze concepts. Qualitative method is employed and the data neededwere collected by observation, in-depth interview, and documentation study.The results of the study show: first, the factors causing political coercion to take placevaried; second, six cases of political coercion in Buleleng Regency did not take place suddenly,but through processes and were related to the cultural coercion inherent within local individualsand groups; third, they took place through semiologic deconstruction related to themeaningfulness provided by the common people and political elites to the ‘pemilu and pilkada’.Thus, the ideologies responsible for political coercion were paternalism, binary opposition ,pragmatism and ‘premanisme’ (the broker of coercion) ; fourth, the implications the cases ofpolitical coercion had on the people in Buleleng Regency were: the pattern of kinship becamebroken, the culture of physical coercion shifted to the culture of symbolic and economiccoercion; a new consensus was established.The conclusions withdrawn in this study show that the characteristics of the politicalcoercion taking place in Buleleng Regency during the reformation era were related to the localcultural values and the pragmatic global cultural values. Such characteristics had wideimplications on the existence of national political cultural system.